Plant conservation in space, time and a changing world: forecasting the fate of Coffea arabica in Ethiopia - Moat, Justin (2018)
We are facing an ever-increasing environmental crisis on our planet, with multiple threats from humankind. Industrialisation, deforestation, overpopulation and exploitation of our natural resources is driving species to extinction and changing the environment we live in. We need to plan for the future in order to adapt or mitigate these risks. Recent advances in computing and analytical techniques, plus the rise of readily available spatial data, provide us with a means to understand the complex interactions between species, environmental change and human activity.